Channel models for optical transmission systems with polarization dependent losses (PDL) - Minoshma, Meena (My University, 2025)
Polarization Dependent Loss (PDL) presents a important transmission impairment in coherent optical communication systems, originating from components such as wavelength selective switches and reconfigurable optical add-drop multiplexers. This thesis develops advanced channel models to characterize the accumulation of PDL across multi-span optical systems, addressing signal propagation, noise interactions, and capacity constraints. Utilizing Jones matrix formulations and singular value decomposition, the study models individual PDL elements and extends the approach to multi-span configurations through recursive signal evolution, incorporating additive white Gaussian noise (AWGN) from amplifiers. Statistical analysis reveals sub-linear PDL growth following Maxwellian distributions, confirmed via Monte Carlo simulations. Noise properties exhibit PDL-induced anisotropy in covariance matrices, quantified by eigenvalue ratios, underscoring performance degradation in long-haul networks. Capacity limits for Gaussian signals indicate losses in high-PDL scenarios. An adapted capacity-achieving scheme, inspired by recent advancements, employs a universal precoder with Linear Minimum Mean Square Error Successive Interference Cancellation (LMMSE-SIC) to transform channels into scalar AWGN subchannels, reducing signal-to-noise ratio (SNR) penalties. Simulations demonstrate enhanced performance compared to standard multiple-input multiple-output (MIMO) approaches, with notable reductions in outage losses. These methodologies provide insights for enhanced system design for reliable long-haul communication. Future investigations could explore nonlinear effects and insertion loss variations, to enable more competitive optical networks in the future.